GREEN CONSUMPTION TERHADAP KEPUTUSAN PEMBELIAN PRODUK FASHION PADA GENERASI MILENIAL - Nurbaity Arrsy, Esty; Permata Nugraha, Intan; Cholilawati, Cholilawati (Universitas Negeri Jakarta, 2021)
This study aims to (1) determine the concept of green consumption that influence the purchasing decisions for fashion products on millennials, (2) to determine the level of purchasing decisions for fashion products on the millennial, (3) to determine the effect of green consumption towards the purchasing decisions for fashion products on millennials. The method used a survey method with a quantitative approach. The samples in this study amounted to 200 respondents taken using incidental sampling techniques with questionnaires distributed online. Data analysis methods used Chi-Square testing. The results of this study indicate that (1) the green consumption variables have a very high value, which is 81.55%. (2) the variable of purchasing decisions has a very high value, 60%. (3) After chi-square testing, the results show that the data of ρ value 0.001 was smaller than the alpha (α) = 0.05 that H0 was rejected, H1 was accepted, so the result indicates that